The Novel Navigation‐Assisted Surgery Increases Financial Burden of Patients Suffering Tile Types B and C Pelvic Fractures in China. - Xing, Jian; Li, Hao-Ran; Wei, Wei; Zhang, Kun; Fu, Ya-Hui; Han, Shuang; Wang, Peng-Fei; Zhuang, Yan; Wesley, Hannah (BioMed Research International, 2025)
Background: Studies demonstrating whether patients with pelvic fractures can benefit from robotic technology in terms of financial burden are lacking. This study was aimed at comparing the financial burden of navigation‐assisted and conventional surgeries for Tile Types B and C pelvic fractures in northwest China. Methods: In total, 188 patients treated at our hospital were included, of whom 140 were treated with navigation‐assisted surgery and 48 with conventional surgery. General, clinical, and economic parameters were compared between the groups. Subgroup analysis stratified by year was performed in the navigation‐assisted surgery group. Results: Fees for pharmaceutical, nursing, and postoperative hospital stay were significantly higher in the conventional surgery group, whereas fees for anesthesia, surgery, total cost, and surgical duration were higher in the navigation‐assisted surgery group. According to the subgroup analysis, fewer patients were treated in the intensive care unit, and more patients suffered severe injuries over time. Conclusion: Compared with conventional surgery, navigation‐assisted surgery was associated with lower fees for pharmaceutical, nursing, and postoperative hospital stays and higher fees for anesthesia, surgery, total cost, and surgical duration. The proportion of pharmaceutical costs and nursing fees, as well as the shorter postoperative recovery time associated with navigation‐assisted surgery, may have a positive impact on patients′ overall economic burden.